Mecanismos de defesa e promoção de crescimento em alface hidropônica por indutores bióticos e abióticos - Faria, Vanessa de Oliveira (2020)
Lettuce is a vegetable of great commercial interest and cultivation in hydroponic systems has become the alternative of many producers for its various advantages, however, this cultivation has some challenges, such as the ease of occurrence of fungal and bacterial epidemics. Resistance induction can become a form of disease management in this system, since it can be induced by biotic or abiotic inducers, which can also promote plant growth by acting as biostimulants. Therefore, the objective of this work was to evaluate the activation of plant defense mechanisms and growth promotion by Azospirillum brasilense, Trichoderma harzianum, acibenzolar-S-metil (ASM, BION ®)and pomegranate extract on curly lettuce grown in a hydroponic system. To evaluate the resistance mechanisms, the activities of the enzymes phenylalanine ammonia lyase (PAL), polyphenoloxidase and peroxidase were used, and for growth promotion data were collected from fresh and dry masses of aerial and root parts, plant height, number of leaves and root volume.For enzymatic activity, treatment with T. harzianum proved to be efficient in inducing peroxidase, polyphenoloxidase and PAL both in the aerial part and the root; ASM increased the activity of peroxidase and PAL in the roots and A. brasilense the activity of peroxidase and polyphenoloxidase in the root. In the growth promotion in the aerial part, A. brasilense showed the greatest increase, followed by the other treatments, and all were superior to the control. In the roots, all treatments promoted growth superior to the control. Therefore, the treatments activated defense enzymes in curly lettuce in a hydroponic system and treatments with A. brasilense and T. harzianum promoted plant growth.